Why HITnet kiosks didn't hit the mark for sexual health education of Western Australian Aboriginal youth - Vujcich, Daniel; Hadland, N.; Sullivan, B.; Clews, Sharon; Kerry, Kathryn; Mak, Donna (2015)
Objective: To assess the use, appropriateness of, and staff feedback on specific sexual health modules, which were installed on Heuristic Interactive Technology (HITnet) kiosks at Aboriginal Community Controlled Health Services (ACCHS). The HITnet kiosks were aimed at Aboriginal youth visiting these sites. Methods: Modules on the HITnet kiosks were assessed for (1) cultural appropriateness using Yunkaporta’s Aboriginal pedagogy framework and (2) compliance with the World Health Organization’s (WHO) advice on key elements for comprehensive sexual health education for young people. Data measuring kiosk use were obtained through HITnet kiosk activity reports. An online survey of ACCHS staff was used to qualitatively assess use of, and staff perceptions of, HITnet kiosks. Results: Kiosk modules were consistent with seven of the eight elements of Yunkaporta’s framework and all of the WHO recommendations. The most popular module generated 3,066 purposeful sessions and the least popular module generated 724 purposeful sessions across nine sites in 2012. While teenagers were the most frequent of the kiosk user groups (39.5% in 2012), the majority of users (56%) were not in the target group (i.e. elders 4%, adults 25%, children 27%). Key issues reported by ACCHS staff (n=11) included: lack of clarity regarding staff responsibility for overseeing kiosk functionality; kiosks attracting “inappropriate ages”; and “lack of privacy” based on kiosk location, screen visibility, and absence of headphones preventing discreet access. Conclusions: The modules were tailored to a young Aboriginal audience through technology thought to be appealing to this group. However, barriers to use of the kiosk included kiosk design features, location, and lack of clarity around responsibility for kiosk operation. Implications: Aboriginal youth need easy access to sexual health messages in a ‘safe’, non-judgmental space. Information and communication that is accessible via personal and mobile devices may be a better vehicle than public kiosks.